Isomorphism between Endomorphism Rings of Modules over A Semisimple Ring - Hery Susanto; Santi Irawati; Indriati Nurul Hidayah; Irawati - (IndoMS, 2020)
Our question is what ring R which all modules over R are determined, up to isomorphism, by their endomorphism rings? Examples of this ring are division ring and simple Artinian ring. Any semi simple ring does not satisfy this property. We construct a semi simple ring R but R is not a simple Artinian ring which all modules over R are determined, up to isomorphism, by their endomorphism rings.